Netflix: defending position as the primary streaming platform of choice - Soltanifar, Mariusz (Henry Stewart Talks, 2020)
An overview of Netflix, Netflix’s challenge, Netflix’s USPs, How did Netflix meet the challenge, Outcomes of Netflix’s actions, What was learned